Canine transmissible venereal tumor immunology: Review - Baldrich, Nicolas; Patiño Quiroz, Beatriz Elena; Losada, Martha Leonor; Fuentes, Cindy (Pubvet, 2021)
Canine Venereal Tumor is one of the few types of contagious tumors described in mammals. It is transplanted as a viable cell allograft into mucous and/or skin, where it triggers an immune process that varies according to the stage of development. The TVT has 4 phases; the phase of progression (P) characterized by the evasion of the histocompatibility barrier and the immune response by immunosuppressive mechanisms, followed by the stagnation phase (E) in which a process of stasis occurs between the tumor and the immune system that allows the remodeling of damaged tissue, in the regression phase (R), the main event is the reactivation of the immune response mediated by infiltrating T lymphocytes and proinflammatory cytokines such as interleukin IL-6 and gamma interferon (IFN- γ), for the removal of the tumor. The Metastasis (M) phase, or tumor spread, develops in non-immunocompetent hosts. This review describes in detail the immune processes carried out in each phase.
Keywords: Canine; tumor; allograft; immunological; phase; histocompatibility